A new in vitro method to evaluate digestibility of commercial diets for dogs. Issue 4 (1st October 2016) - Biagi, Giacomo; Cipollini, Irene; Grandi, Monica; Pinna, Carlo; Vecchiato, Carla Giuditta; Zaghini, Giuliano
Abstract: The aim of the present study was to develop a new in vitro method for evaluating the digestibility of commercial diets for dogs. First, in order to develop the in vitro method, the digestibility of four commercial diets for dogs was evaluated through several in vitro trials and results were compared with those that were retrieved from the literature. The in vitro method that was developed consists of two incubation phases, a first lasting 2h and taking place in the presence of pepsin, gastric lipase and HCl (gastric phase) and a second 4h one with pancreatin and bile salts (intestinal phase). Later, digestibility of 16 extruded diets for dogs was evaluated both in vivo with adult dogs and in vitro . There was a close linear relationship between in vivo total tract and in vitro dry matter digestibility ( r 2 = .81), whereas accuracy of crude protein digestibility using the in vitro method was lower ( r 2 = .51). Linear regression accuracy for ether extract and starch digestibility was low, but the digestibility results obtained with the in vitro method (95.3 and 98.7% for ether extract and starch, respectively) were very close to those from the in vivo trial (average digestibility of ether extract and starch was 94.8 and 99.1%, respectively). The present in vitro method has proved to be a relatively simple, quick procedure for predicting the digestibility of commercial diets for dogs. The utilisation of such a method may significantly reduce the need for in vivo digestion trials with dogs.